An Increasing Growth Of Oil Palm Plants Based A Mixture Nitrogen And Potassium Chemicals - Asmara Sari Nasution; Efi Said Ali (Jurnal Scientia, 2024)
This research aims to test the concentration of POC Nitrogen and POC Potassium on the growth of oil palm plant seeds (Elaeis guineensis Jacq). The method used in this research was a Randomized Group Design (RAK) which consisted of 2 treatment factors. The first treatment is the POC Nitrogen Concentration Test which consists of N0=Control, N1= 1%, N2= 2%, N3= 3%. The second treatment is the POC Potassium Concentration Test K0=Control, K1=1%, K2=2% and K3=3%. The parameters observed were plant height (cm), number of leaves (strands), leaf width (cm) and stem diameter (cm). The research results showed that the POC Nitrogen Concentration Test had a significant effect on the parameters of plant height (cm), number of leaves (cm) and leaf width (cm) but had no significant effect on the stem diameter parameter (cm). In the POC Potassium Concentration Test, it showed a real influence on the stem diameter parameter (cm) but an insignificant effect on the parameters of plant height (cm), number of leaves (strands) and leaf area (cm). The interaction between the POC Nitrogen and POC Potassium Concentration Tests showed unreal results for each observation parameter.